INCREASING STUDENTS’ MASTERY OF ENGLISH VOCABULARY THROUGH SONGS - Aldo I.; Noldy Palenkahu; Sarah Kamagi (SoCul: International Journal of Research in Social Cultural Issues, 2021)
This research aimed at finding out whether the use of songs could increase the students’ mastery of vocabulary or not. In conducting this research, quantitative research was used. The subject of this study was one class of the second grade at SMP Anugrah Tondano that consist of 20 students. The instrument of collecting data was in the form pre-test and post-test. The tests were in the form fill in test with missing words. The result of this research showed that the mean scores in the post-test was higher (70,5) than those of pre-test (40). it could be concluded that, the use of song was effective to increase students’ vocabulary mastery because it could be stimulated students in learning and encourage them to be able to memorize the word. Keywords: Vocabulary, Song lyrics, Increasing